Know before whom you stand: Mikael Enckell's Companions of the Unknown [Okändhetens följeslagare]. Issue 2 (2nd July 2016) - Titelman, David
ABSTRACT: Mikael Enckell's book is discussed as a combined self-analytic tour de force and psychoanalytic supplement to Jewish philosophy represented by Frans Rosenzweig and others. The author discusses Enckell's views on the roots of psychoanalysis in Jewish thought, anti-Semitism, historiography, the importance of human dialogue, revelation and psychic integration, atheism, and the nature of recovery in psychoanalysis. Enckell's views of a triad of human activities open to conflict and ambiguity – Judaism, poetry, and psychoanalysis – are supplemented by a short discussion on the role of annihilation anxiety in these areas.